The Impact of First Childbirth Experience on Women’s Attitude Towards Having Another Child and Subsequent Vaginal Birth - Ghanbari-Homayi, Solmaz; Mohammad-Alizadeh-Charandabi, Sakineh; Meedya, Shahla; Jafarabadi, Mohammad A.; Mohammadi, Eesa; Mirghafourvand, Mojgan (Current Women's Health Reviews, 2021)
Background: Some women may consider childbirth an unpleasant event, which can influence their decisions on subsequent pregnancies and type of birth. Objective: The aim of this study was to determine the proportion of negative childbirth experience and its relationship with women’s attitudes towards subsequent pregnancy and vaginal birth. Methods: The study design was cross-sectional. A cluster sampling was used to recruit 800 primiparous women from health centers in Tabriz, Iran. The Persian version of the Childbirth Experience Questionnaire was used to assess women’s childbirth experiences. Univariate and multivariate logistic regression was used to assess the impact of childbirth experiences on women’s attitudes towards subsequent pregnancy and vaginal birth. Results: Thirty-seven percent of women reported a negative childbirth experience. There was a statistically significant relationship between childbirth experience and the attitude of women towards subsequent pregnancy (p<0.001) and vaginal birth (p<0.001). By controlling the effects of potential confounding variables such as socio demographic characteristics, negative childbirth experience was found to be an independent predictive factor for women’s reluctance towards subsequent pregnancies [OR= 0.42 (CI 95%: 0.57 to 0.31), p<0.001] and vaginal birth [OR= 0.08 (CI 95%: 0.14 to 0.04); p<0.001]. Conclusion: Negative childbirth experience is associated with a reduced willingness for women to get pregnant again and have vaginal birth. It is recommended that key stakeholders pay attention to strategies to improve childbirth experiences among primiparous women in Iran.
Keywords: reproductive behavior